Intranasal rifampicin for Alzheimer's disease prevention. Issue 1 (13th July 2018) - Umeda, Tomohiro; Tanaka, Akiko; Sakai, Ayumi; Yamamoto, Akira; Sakane, Toshiyasu; Tomiyama, Takami
Abstract: Introduction: Oral rifampicin has been shown to significantly reduce amyloid β (Aβ) and tau pathologies in mice. However, it shows occasional adverse effects such as liver injury in humans, making its use difficult for a long period. Methods: To explore safer rifampicin treatment, APPOSK mice, a model of Alzheimer's disease, were treated with rifampicin for 1 month via oral, intranasal, and subcutaneous administration, and its therapeutic efficacy and safety were compared. Results: Intranasal or subcutaneous administration of rifampicin improved memory more effectively than oral administration. The improvement of memory was accompanied with the reduction of neuropathologies, including Aβ oligomer accumulation, tau abnormal phosphorylation, and synapse loss. Serum levels of a liver enzyme significantly rose only by oral administration. Pharmacokinetic study revealed that the level of rifampicin in the brain was highest with intranasal administration. Discussion: Considering its easiness and noninvasiveness, intranasal administration would be the best way for long‐term dosing of rifampicin.